1995
DOI: 10.1002/bies.950170810
|View full text |Cite
|
Sign up to set email alerts
|

Instability of inhibited replication forks in E. coli

Abstract: Inhibiting the progress of replication forks in E. coli makes them susceptible to breakage. Broken replication forks are evidently reassembled by the RecBCD recombinational repair pathway. These findings explain a particular pattern of DNA degradation during inhibition of chromosomal replication, the role of recombination in the viability of mutants with displaced replication origin, and hyper-recombination observed in the Terminus of the E. coli chromosome in rnh mutants. Breakage and repair of inhibited repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 64 publications
1
59
0
Order By: Relevance
“…In particular, bacterial and yeast RecQ helicases seem to be involved in the suppression of illegitimate recombination after collapse and disassembly of the replication fork, caused either by replication arrest or DNA damage (reviewed by Kuzminov, 1995;Chakraverty and Hickson, 1999;Michel, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, bacterial and yeast RecQ helicases seem to be involved in the suppression of illegitimate recombination after collapse and disassembly of the replication fork, caused either by replication arrest or DNA damage (reviewed by Kuzminov, 1995;Chakraverty and Hickson, 1999;Michel, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…One surprising example of the need to carry out this rigorous scrutiny comes from the study of recBC mutants, which are deficient in double-strand-break repair. Based on their UV-sensitive phenotype and poor viability during growth, it was initially speculated that replication forks may frequently collapse to form double-strand breaks at DNA lesions and that RecBC was then required for replication recovery (60). However, multiple studies, including our own, have reported that the recovery of replication occurs quite normally in recBC mutants following UV irradiation, despite their hypersensitivity (21,53,61).…”
Section: A Common Pathway Involving Both Nucleotide Excision Repair Amentioning
confidence: 96%
“…Blocks to replication can stimulate illegitimate recombination and deletions in E. coli (42). Paused replication forks can lead to double-strand breaks (41,43,44) and there is evidence of increased mutagenesis in the local region of doublestrand breaks (45). Essential genes are greatly enriched among transcripts cooriented with replication (20,21), probably because cells are more sensitive to mutations in essential genes and it is important to avoid disruption of their replication by head-on transcription (11).…”
Section: Selective Pressures For Coorientation Of Transcription and Rmentioning
confidence: 99%